Digital Transformation and Employment in Micro and Small Industries: Evaluating the Impact of E-Commerce Adoption in Indonesia - Shalih, Muhammad; Hartono, Djoni (Jurnal Ekonomi Pembangunan, 2025)
This study aims to evaluate the impact of e-commerce adoption on employment absorption in micro and small manufacturing enterprises (IMK) in Indonesia. Utilizing data from the 2022 Micro and Small Industry Survey conducted by Statistics Indonesia, the analysis employs a Propensity Score Matching approach to address the imbalance in characteristics between e-commerce adopters and non-adopters. The results indicate that e-commerce adoption is positively associated with an increase in the number of workers employed by adopting firms. Business characteristics such as the presence of professional workers, business legality, and firm age are found to significantly influence adoption. Sensitivity analysis also shows that the estimates are robust against potential hidden bias. These findings highlight the importance of policy interventions that promote e-commerce adoption among IMK as a strategic effort to enhance employment capacity. Policy implications drawn from this study emphasize the need for cost-effective digital training programs, improved digital literacy, accelerated business formalization, and sectoral as well as business-cycle-based approaches to maximize the impact of e-commerce on employment in the IMK sector. With the right and targeted interventions, digitalization in the IMK sector has the potential not only to increase labor absorption but also to contribute to more inclusive and sustainable economic growth.